Ribosomes guide pachytene piRNA formation on long intergenic piRNA precursors - Sun, Yu H.; Zhu, Jiang; Xie, Li Huitong; Li, Ziwei; Meduri, Rajyalakshmi; Zhu, Xiaopeng; Song, Chi; Chen, Chen; Ricci, Emiliano P.; Weng, Zhiping; Li, Xin Zhiguo (Nature cell biology, 2020)
PIWI-interacting RNAs (piRNAs) are a class of small non-coding RNAs essential for fertility. In adult mouse testes, most piRNAs are derived from long single-stranded RNAs lacking annotated open reading frames (ORFs). The mechanisms underlying how piRNA sequences are defined during the cleavages of piRNA precursors remain elusive. Here, we show that 80S ribosomes translate the 5′-proximal short ORFs (uORFs) of piRNA precursors. The MOV10L1/Armitage RNA helicase then facilitates the translocation of ribosomes into the uORF downstream regions (UDRs). The ribosome-bound UDRs are targeted by piRNA processing machinery, with the processed ribosome-protected regions becoming piRNAs. The dual modes of interaction between ribosomes and piRNA precursors underlie the distinct piRNA biogenesis requirements at uORFs and UDRs. Ribosomes also mediate piRNA processing in roosters and green lizards, implying that this mechanism is evolutionarily conserved in amniotes. Our results uncover a function for ribosomes on non-coding regions of RNAs and reveal the mechanisms underlying how piRNAs are defined. Sun et al. uncover a conserved mechanism by which ribosomes function in defining the position of pachytene piRNA formation on long single-stranded RNAs during spermatogenesis.